Persistent confirmed low-grade dysplasia in Barrett's esophagus is a risk factor for progression to high-grade dysplasia and adenocarcinoma in a US Veterans cohort. Issue 2 (5th July 2019) - Song, K Y; Henn, A J; Gravely, A A; Mesa, H; Sultan, S; Shaheen, N J; Shaukat, A; Hanson, B J
SUMMARY: Patients with Barrett's esophagus (BE) and low-grade dysplasia (LGD) are at increased risk of esophageal adenocarcinoma (EAC), although many regress to nondysplastic BE. This has significant clinical importance for patients being considered for endoscopic eradication therapy. Our aim is to determine the risk for progression in patients with confirmed persistent LGD. We performed a single-center retrospective cohort study of patients with BE and confirmed LGD between 2006 and 2016. Confirmed LGD was defined as LGD diagnosed by consensus conference with an expert GI pathologist or review by an expert GI pathologist and persistence as LGD present on subsequent endoscopic biopsy. The primary outcome was the incidence rate of HGD (high-grade dysplasia)/EAC. Secondary outcomes included risk factors for dysplastic progression. Risk factors for progression were assessed using univariate and multivariate analysis with logistic regression. Of 69 patients (mean age 65.2 years) with confirmed LGD were included. In total, 16 of 69 patients (23.2%) with LGD developed HGD/EAC during a median follow-up of 3.74 years (IQR, 1.24–5.45). For persistent confirmed LGD, the rate was 6.44 (95% confidence interval (CI), 2.61–13.40) compared to 2.61 cases per 100 patient-years (95% CI, 0.83–6.30) for nonpersistent LGD. Persistent LGD was found in only 29% of patients. Persistent LGD was an independent risk factor for the development of HGD/EAC (OR 4.18; [95% CI, 1.03–17.1]). Persistent confirmed LGD, present in only 1/3 of patients, was an independent risk factor for the development of HGD/EAC. Persistence LGD may be useful in decision making regarding the management of BE.